2009
DOI: 10.1073/pnas.0905778107
|View full text |Cite
|
Sign up to set email alerts
|

G protein–coupled receptor kinase 2 (GRK2) modulation and cell cycle progression

Abstract: Cell cycle progression requires changes in the activity or levels of a variety of key signaling proteins. G protein-coupled receptor kinase 2 (GRK2) plays a central role in G protein-coupled receptor regulation. Recent research is uncovering its involvement in additional cellular functions, but the potential role of GRK2 in the cell cycle has not been addressed. We report that GRK2 protein levels are transiently down-regulated during the G2/M transition by a mechanism involving CDK2-mediated phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 30 publications
8
99
0
1
Order By: Relevance
“…Possibly, GRK2 phosphorylates cytoplasmic tubulin or other proteins that would enter the cilium and modulate microtubule organization. Alternatively, recent studies have shown that temporary down-regulation of GRK2 is required for normal cell cycle progression (34) and that depletion of ␤-arrestin results in uncontrolled cell proliferation and reduced cilia numbers (35), suggesting an indirect mechanism involving cell cycle control. Yet, other mechanisms can certainly not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, GRK2 phosphorylates cytoplasmic tubulin or other proteins that would enter the cilium and modulate microtubule organization. Alternatively, recent studies have shown that temporary down-regulation of GRK2 is required for normal cell cycle progression (34) and that depletion of ␤-arrestin results in uncontrolled cell proliferation and reduced cilia numbers (35), suggesting an indirect mechanism involving cell cycle control. Yet, other mechanisms can certainly not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Besides phosphorylating activated GPCRs, GRK2 is functionally related to several members of the receptor tyrosine kinase family, phosphorylates a variety of nonreceptor substrates, and dynamically interacts with other important signal transduction partners in a manner that is independent of its kinase activity (4,5). For instance, as emphasized in this slide, in the past few years our group has reported GRK2 interactions with the mitogen-activated or extracellular signal-regulated protein kinase kinase MEK (6), the MAPK p38 (7), the ARF (adenosine diphosphate ribosylation factor) GTPase (guanosine triphosphatase)-activating protein GIT1 (8), Mdm2 (9), the prolyl-isomerase Pin1 (10), and insulin receptor substrate 1 (IRS1) (11). Some of these interactions underlie the participation of GRK2 in basic cellular processes such as cell cycle progression (10), cell migration (8), and insulin resistance (11).…”
mentioning
confidence: 92%
“…Recent research further explains that ADRBK1 contributes to an orchestrated G 2 /M checkpoint function and thereby restricts the apoptotic fate of the arrested cells due to DNA damage. 19 Our results clearly indicated that the ADRBK1 knockdown in MDA-MB-231 cells led to cell cycle arrest at G 0 /G 1 phase, which potentially provided the explanation for cell growth inhibition. Previous evidence and this study strongly suggest that ADRBK1 is a critical factor for cell growth due to its apoptotic inhibitory actions.…”
Section: Discussionmentioning
confidence: 73%